Еволюція методології дизайн-мислення під впливом розвитку генеративного штучного інтелекту - Новаковський, А. В. (ХНУРЕ, 2024)
The paper sets the stage to explore the evolution of the Design Thinking methodology under the influence of the rapid development of Generative AI technologies. It provides a concise overview of the key benefits and challenges that have already been identified in early research publications on augmenting design processes with GenAI tools. The authors (1) emphasize the need to develop a comprehensive research framework for understanding the multifaceted nature of Generative AI’s influence on design and creativity and (2) propose the concept of such a framework based on decomposing Design Thinking into four interrelated layers.
Keywords: дизайн-мислення; генеративний штучний інтелект